Woman Was Made for Joy and Woe: Three Sonic Meditation-Homages - Shurland, Rachel. (Tufts University. Tisch Library., 2023)
Thesis (M.A.)--Tufts University, 2023.; Submitted to the Dept. of Music.; Advisor: Paul Lehrman.; Committee: John McDonald, and Joe Auner.; Keyword: Musical composition.